DIFFERENCES IN THE ZAKAT SYSTEM IN QATAR AND INDONESIA - Bella Delima; Maryam Batubara; Dea Sarah Sati Hana'an (PT. Radja Intercontinental Publishing, 2024)
Zakat as an Islamic financial instrument has an important position in alleviating poverty, in managing zakat in Indonesia and Qatar. This research aims to provide an explanation of zakat management in Qatar and Indonesia. The practice of collecting and distributing zakat in Qatar involves several approaches, including direct payment by individuals, distribution through families, and through charitable organizations such as Qatar Charity. Despite efforts to increase transparency, politicization still influences some aspects, and Qatari regulations emphasize government control over zakat to direct it in line with state interests. This research suggests that there are differences in the management of zakat in the two countries, differences in various ways. Namely regulations, institutions, managers, supervisory institutions, models for implementing and collecting zakat, management of collection and distribution.